Analysis of Parameter Roasting on Color and Peanuts Roasted Taste - Silvi Ari Yanti; Chandrasa Soekardi; M. Sobron Yamin Lubis (Aceh International Journal of Science and Technology, 2018)
The purpose of this study is to determine the optimum temperature of roasting, optimal rotation speed of tube and roasting time, to produce roasted peanuts with good taste and good colour. The research method is experimental using a Completely Randomized Design (CRD) with three factors of temperature, rotation and time. And analyzed using Anova method and Multiple Linear Regression. Temperature consists of five variables, namely 80oC, 85oC, 90oC, 95oC and 100oC. For rotations speed consists of 30, 35, 40 and 45 RPM. Variable of roasting time consists of four roasting times of 10, 15, 20 and 25 minutes. The numbers of data were 80 experiments. With three observation parameters namely moisture containing, color and aroma. It can be concluded that the temperature 95oC is the optimal roasting temperature; the optimal rotation speed is 40 RPM and 25 minutes for each roasting time. With the variable values mentioned, roasted bean products contain a fairly good taste, good moisture and good colour.